CSF1 overexpression promotes high-grade glioma formation without impacting the polarization status of glioma-associated microglia and macrophages - De, Ishani (Cancer Res, 2016)
Current therapies for high-grade gliomas extend survival only modestly. The glioma microenvironment, including glioma-associated microglia/macrophages (GAMs), is a potential therapeutic target. The microglia/macrophage cytokine CSF1 and its receptor CSF1R are overexpressed in human high-grade gliomas. To determine if the other known CSF1R ligand IL-34 is expressed in gliomas, we examined expression array data of human high-grade gliomas and performed RT-PCR on glioblastoma sphere-forming cell lines (GSCs). Expression microarray analyses indicated that CSF1, but not IL-34, is frequently overexpressed in human tumors. We found that while GSCs did express CSF1, most GSC lines did not express detectable levels of IL-34 mRNA. We therefore studied the impact of modulating CSF1 levels on gliomagenesis in the context of the GFAP-V12Ha-ras-IRESLacZ (Ras*) model. Csf1 deficiency deterred glioma formation in the Ras* model while CSF1 transgenic overexpression decreased the survival of Ras* mice and promoted the formation of high-grade gliomas. Conversely, CSF1 overexpression increased GAM density, but did not impact GAM polarization state. Regardless of CSF1 expression status, most GAMs were negative for the M2 polarization markers ARG1 and CD206; when present, ARG1+ and CD206+ cells were found in regions of peripheral immune cell invasion. Therefore, our findings indicate that CSF1 signaling is oncogenic during gliomagenesis through a mechanism distinct from modulating GAM polarization status.